2015
DOI: 10.1186/s40104-015-0005-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the quality of feed fats and oils and their effects on pig growth performance

Abstract: Feed fats and oils provide significant amounts of energy to swine diets, but there is large variation in composition, quality, feeding value, and price among sources. Common measures of lipid quality include moisture, insolubles, and unsaponifiables (MIU), titer, and free fatty acid content, but provide limited information regarding their feeding value. Lipid peroxidation is an important quality factor related to animal growth performance and health, but maximum tolerable limits in various lipids have not been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
68
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 46 publications
3
68
1
2
Order By: Relevance
“…Studies evaluating the impact of peroxidized oils in livestock have shown variable results, including no effects on growth performance of rabbits [6], a reduction in feed intake in sheep [7], pigs, and broilers [8], a reduction in growth of pigs [9][10][11][12][13], broilers [8,14,15], and rats [16], increased morbidity and mortality in pigs [17], reduced oxidative stability of pork [18], no oxidative effects of sheep meat [19], alteration of the nutritional quality of chicken and rabbit meat [20], and compromised oxidative status in animals [4,[14][15][16]21] causing degradation of cellular components, including protein, lipids, and DNA [15,21].…”
Section: Introductionmentioning
confidence: 99%
“…Studies evaluating the impact of peroxidized oils in livestock have shown variable results, including no effects on growth performance of rabbits [6], a reduction in feed intake in sheep [7], pigs, and broilers [8], a reduction in growth of pigs [9][10][11][12][13], broilers [8,14,15], and rats [16], increased morbidity and mortality in pigs [17], reduced oxidative stability of pork [18], no oxidative effects of sheep meat [19], alteration of the nutritional quality of chicken and rabbit meat [20], and compromised oxidative status in animals [4,[14][15][16]21] causing degradation of cellular components, including protein, lipids, and DNA [15,21].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is an urgent need to return to a balanced fatty acid diet by decreasing the intake of cholesterol and saturated fats (48). It has been found that the oxidative modification of lipids, which are susceptible to peroxidation, degrades animal productivity and meat quality (49,50). Towards this direction, a herbal extract mixture administered to animals has been shown to significantly increase the content of polyunsaturated fatty acids (PUFAs), creating meat with beneficial health properties which is less susceptible to oxidation (51).…”
Section: Regulation Of Redox Status and Farm Animal Meat Qualitymentioning
confidence: 99%
“…It is also well known that high level of dietary fat negatively impacts gut integrity and function, especially modified function and morphology of the small intestine of piglets (Shurson, Kerr, & Hanson, ). In turn, inulin is one of the prebiotics affecting the composition of gut microbiota and stimulates the growth of Bifidobacteria and/or Lactobacilli, which increases the absorption of nutrients in the intestines (Pouyamanesh, Amoli, Yaghmaei, & Ebrahim‐Habibi, ).…”
Section: Introductionmentioning
confidence: 99%